Diversity and population structure of Marine Group A bacteria in the Northeast subarctic Pacific Ocean - Allers, Elke (Nature Publishing Group, 2013)
Marine Group A (MGA) is a candidate phylum of Bacteria that is ubiquitous and abundant in the ocean. Despite being prevalent, the structural and functional properties of MGA populations remain poorly constrained. Here, we quantified MGA diversity and population structure in relation to nutrients and O(2) concentrations in the oxygen minimum zone (OMZ) of the Northeast subarctic Pacific Ocean using a combination of catalyzed reporter deposition fluorescence in situ hybridization (CARD-FISH) and 16S small subunit ribosomal RNA (16S rRNA) gene sequencing (clone libraries and 454-pyrotags). Estimates of MGA abundance as a proportion of total bacteria were similar across all three methods although estimates based on CARD-FISH were consistently lower in the OMZ (5.6%±1.9%) than estimates based on 16S rRNA gene clone libraries (11.0%±3.9%) or pyrotags (9.9%±1.8%). Five previously defined MGA subgroups were recovered in 16S rRNA gene clone libraries and five novel subgroups were defined (HF770D10, P262000D03, P41300E03, P262000N21 and A714018). Rarefaction analysis of pyrotag data indicated that the ultimate richness of MGA was very nearly sampled. Spearman's rank analysis of MGA abundances by CARD-FISH and O(2) concentrations resulted in significant correlation. Analyzed in more detail by 16S rRNA pyrotag sequencing, MGA operational taxonomic units affiliated with subgroups Arctic95A-2 and A714018 comprised 0.3–2.4% of total bacterial sequences and displayed strong correlations with decreasing O(2) concentration. This study is the first comprehensive description of MGA diversity using complementary techniques. These results provide a phylogenetic framework for interpreting future studies on ecotype selection among MGA subgroups, and suggest a potentially important role for MGA in the ecology and biogeochemistry of OMZs.